The effect of non-thermal plasma treatment on wheat germination and early growth - Dobrin, Daniela; Magureanu, Monica; Mandache, Nicolae Bogdan; Ionita, Maria-Daniela (Innovative food science & emerging technologies, 2015)
The influence of non-thermal plasma treatment on wheat seeds (Triticum aestivum) has been investigated using a surface discharge reactor at atmospheric pressure and room temperature. Growth parameters, like roots and sprouts length and dry weight were measured on the fourth day of germination and a Gaussian distribution was used for curve-fitting of the obtained results. It was found that plasma had little effect on the germination rate, but influenced growth parameters. In the case of plasma treated seeds, the distribution of roots was shifted towards higher lengths as compared with the untreated samples. The distribution of the sprouts length was about two times narrower for the treated samples as compared with the control seeds. The sprouts and roots of the plasma treated seeds were heavier than those of the control samples. The root-to-shoot (R/S) ratio differed substantially, being 0.88±0.016 for the untreated seeds and reaching 1.2±0.005 for the treated samples. The results obtained in this research demonstrate that non-thermal plasma treatment has a positive effect on wheat early growth. Due to its advantages (uniform treatment, no destruction of seeds, no requirement for chemicals), plasma might become an effective alternative to traditional pre-sowing seed treatment used in agriculture. •Positive effect of non-thermal plasma treatment on the early growth of wheat seeds•Longer and heavier roots of plasma treated seeds•Significantly increased root-to-shoot ratio after plasma treatment•Increased wettability for the plasma treated seeds